2000
DOI: 10.1017/s0033291799001877
|View full text |Cite
|
Sign up to set email alerts
|

The effects of trauma among kidnap victims in Sardinia, Italy

Abstract: There is no significant connection between PTSD and the Stockholm syndrome. Both are indices of the severity of the trauma of being kidnapped, but they are associated with different aspects of the traumatic experience. The presence of both syndromes appears to have a detrimental effect on physical health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 18 publications
1
32
0
3
Order By: Relevance
“…the child becomes the "bad object" so as to maintain the fantasy of the parents as the "good object" (19). Among adults undergoing trauma, such as kidnap victims, this process of taking on excessive responsibility for the traumatic actions of one's perpetrator has been labeled Stockholm Syndrome (20).…”
Section: Stage I "Can I Be Safe Here?" Establishing the Treatment Almentioning
confidence: 99%
“…the child becomes the "bad object" so as to maintain the fantasy of the parents as the "good object" (19). Among adults undergoing trauma, such as kidnap victims, this process of taking on excessive responsibility for the traumatic actions of one's perpetrator has been labeled Stockholm Syndrome (20).…”
Section: Stage I "Can I Be Safe Here?" Establishing the Treatment Almentioning
confidence: 99%
“…This is like other situations in which intense relationships develop during crises: front-line soldiers, resistance fighters in the Second World War, and even the Stockholm syndrome, 21 in which hostages paradoxically form close ties with their captors.…”
Section: Discussionmentioning
confidence: 71%
“…Although this is a small study, the fact that all respondents found the group helpful and felt it would be beneficial to replicate this across a wide range of specialties suggests that this model could be usefully employed in hospitals. Senior palliative care physicians, too, may be affected by stress, 21,22 and Farnham (personal communication, 2004) has shown that his consultant support group has been successful.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistics and anecdotes of the kidnapping process are discussed. Favaro et al (2000) conduct interviews with 24 Sardinian kidnap victims to assess mental health effects. They identify enhanced rates of post-traumatic stress disorder and Stockholm syndrome.…”
Section: Literature Reviewmentioning
confidence: 99%